MOTIVASI KERJA IBU RUMAH TANGGA PADA USAHA HOME INDUSTRI TEMPE DI KELURAHAN LABUH BARU BARAT KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Syarifah Andini; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The formulation problem of this research is “How is The Work Motivation of Housewives on Fermented Soybean Home Industry at Kelurahan Labuh Baru Barat Kecamatan Payung Sekaki Kota Pekanbaru”. This type of research is descriptive naturalistic with a qualitative approach to find out the work motivation of housewives on fermented soybean home industry business at kelurahan labuh baru kecamatan payung sekaki kota pekanbaru. This research is consist of one variable that is work motivation with research indicator (1) Human relationships (2) working conditions (3) salary (4) Achievement (5) responsibility (6) Recognition. The subjects of this study are 6 people consisting of 2 core informants, 3 control informants, and 1 informant observer. Technique Data collection is by performing participatory observation, interview, and documentation. Based on the results of interviews with informants, the findings of the data show that through the six indices, it is clear that things that work motivation of housewives on fermented soybean home industry business at kelurahan labuh baru kecamatan paying sekaki kota pekanbaru is salary that earned to complete the whole family’s daily needs, food, and board. In addition, the human relationship can be concluded by the relationship of the workers together with well maintained environment, as well as with the responsibility toward work that always well maintained, so the result that obtained besides salary is recognition that given by manager or other people. Either praises or other achievements. Meanwhile, if you look at the work performance, only 1 informant that doesn’t have a good condition, it is due to informant condition being pregnant, make the working time become limited. Based on the results of the data, it can be concluded that work motivation of housewives on fermented soybean home industry business at kelurahan labuh baru kecamatan paying sekaki kota pekanbaru has succeeded in doing good both directly and indirectly. This is indicated by none of obstacles in the field. Recommendation aimed to Government to be willing to invest for fermented soybean home industry business at kelurahan labuh baru kecamatan paying sekaki kota pekanbaru for housewives who work on the business, in order to apply new ideas to create and develop fermented soybean home industry.Keywords: Work Motivation, Housewives, Fermented Soybean Home Industry